EFEKTIFITAS PENGGUNAAN STRATEGI THINK TALK WRITE BERBANTUAN AUDIO VISUAL TERHADAP HASIL BELAJAR MTS AR-ROHMAN - Nuraini, Nuraini; Sulistyarini, Sulistyarini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract       This study aims to determine the planning effectiveness of the use of audio visual assisted Think Talk Write strategies on student learning outcomes in Ips subjects in VIII Mts Ar rohman Village Kapur Village Kubu Raya District. The method used in the study was an experimental method with a quasi-experimental research form (experimental research quasy). The source of this research data is the eighth grade students of MTs Ar rohman and the data are the students' answer sheets of the material in the form of environmental damage and the results of interviews with the VIII Grade Ips Teacher. The results of this study are the average results of the post-test class before 71.00 and TTW class 76.60. Judging from the completeness, students who complete the class before as many as 13 students and TTW classes as many as 17 students based on the U Whitney test on the class test post before and TTW class obtained a significance value of 0.05 <(0.00 <0.05), then there is a difference the results of the previous class posttest and TTW classes. It is known that there is a difference between the results of the class before and the TTW class, so Ho is rejected and Ha is accepted. That TTW class is higher in post test results than before class, TTW class with TTW strategy model while class before using TTW learning. So the TTW strategy model is more effective than Question and Answer learning, to improve the social studies learning outcomes of VIII grade MTs Ar Rohman Kapur Village. How big is the effect of the learning model used by the effect size formula. effect size was obtained 1.8. Then based on the criteria that apply the effect size value is included in the large category. Keywords: TTW Strategy, Learning Outcomes